A coastal flooding database from 1980 to 2018 for the continental Portuguese coastal zone. (October 2021) - Tavares, Alexandre Oliveira; Barros, José Leandro; Freire, Paula; Santos, Pedro Pinto; Perdiz, Luís; Fortunato, André Bustorff
Abstract: Continental Portugal presents an extensive and diversified coastal zone which concentrates the main public and private infrastructures of the different economic sectors, as well as the main critical infrastructures. This area is also characterized by a high population density, being a differentiated territory in geophysical, biological and landscape terms. The wave regime is highly energetic, and storms are frequent. In the last decades, the coast of continental Portugal has been affected numerous times by overtopping and coastal flooding processes. Identifying the critical coastal typologies affected by flooding can contribute to a comprehensive flood risk management framework for the Portuguese coastal zones. Hence, a historical database of coastal flooding occurrences was created for the period 1980–2018 based on national and regional newspapers. For this period 650 occurrences were identified as well as 1708 impacts associated with them. In terms of impacts, the typologies associated with public areas, human impacts, the natural system, environmental degradation and buildings stand out. Results provide relevant temporal and spatial information about coastal historical flood occurrences related to extreme storm events and associated impacts, and contribute to the design of a risk framework. Highlights: Identification and evaluation of the different occurrences of coastal flooding. The database is characterized by its interdisciplinary, consistency, and user-friendliness. Inclusion of the flooding forcing conditions as a basis of hemerographic analysis. The methodology adopted allowed the identification of different coastal typologies. Increase in the number of occurrences and associated impacts between 2010 and 2018.